2019
DOI: 10.12659/msm.916428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bone Marrow-Derived Mesenchymal Stem Cells on Hypoxia and the Transforming Growth Factor beta 1 (TGFβ-1) and SMADs Pathway in a Mouse Model of Cirrhosis

Abstract: Background: The role of bone marrow-derived mesenchymal stem cells (BM-MSCs) in liver fibrosis remains poorly understood. This study aimed to use a mouse model of carbon tetrachloride (CCL 4)-induced liver fibrosis to investigate the effects of BM-MSCs during liver hypoxia and the involvement of the transforming growth factor beta 1 (TGF-b1) and SMADs pathway. Material/Methods: Thirty C57BL/6 mice were randomly divided into the control group (n=10), the model group (n=10), and the BM-MSC-treated model group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…To restore liver functionality in patients with liver cirrhosis, cell therapy strategies using bone marrow-derived stem cells [ 6 , 27 ] or MSCs carrying specific genes are sought-after research areas [ 5 , 9 ]. The treatment with MSCs alone showed some degree of alleviation of liver fibrosis and also inhibited HSC proliferation, which is in accordance with the studies in mouse or rat models [ 10 , 28 , 29 ]. Here we have firstly validated the effectiveness of cell therapy using MSCs overexpressing the Smad7 gene on the CCl 4 -induced in vivo animal model.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To restore liver functionality in patients with liver cirrhosis, cell therapy strategies using bone marrow-derived stem cells [ 6 , 27 ] or MSCs carrying specific genes are sought-after research areas [ 5 , 9 ]. The treatment with MSCs alone showed some degree of alleviation of liver fibrosis and also inhibited HSC proliferation, which is in accordance with the studies in mouse or rat models [ 10 , 28 , 29 ]. Here we have firstly validated the effectiveness of cell therapy using MSCs overexpressing the Smad7 gene on the CCl 4 -induced in vivo animal model.…”
Section: Discussionsupporting
confidence: 89%
“…MSCs can promote liver regeneration and suppress liver fibrosis and thus may partially recover liver function and retard the progression of liver cirrhosis [ 6 ]. This new approach has been considered as potentially the most effective non-surgical treatment for liver cirrhosis [ 6 , 7 ]; however, clinical trials using stem cells seem to not be so successful [ 5 , 8 10 ]. Therefore, development of stem cells carrying a specific gene related to the regulation of fibrosis could be a new direction for cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, IL-6 stimulates the activation of STAT3 and increases collagen mRNA expression in HSCs; the phosphorylation of STAT3 activates the TGF-β cascade through SMAD3 activation (O'Reilly et al, 2014). In this framework, Zhang et al (2019) demonstrated that BM-MSCs reduced fibrosis by modulating the TGF-β1/SMADs signaling. Yuan et al (2019) showed that the low amount of collagen deposition was related to low IL-6 mRNA levels and the reduction was evident especially for type III collagen α1.…”
Section: Msc Treatment Counteracts Liver Fibrosis Developmentmentioning
confidence: 95%
“…These beneficial effects were correlated with a modulation of the TGF-β1/SMADs signaling pathway in liver cells. In particular, BM-MSCs reduced TGF-β1 and SMAD3 expression and increased SMAD7 expression (Zhang et al, 2015(Zhang et al, , 2019. SMAD7 can be regulated by different stimuli, including TGF-β, IFN-γ, and TNF-α.…”
Section: Msc Treatment Counteracts Liver Fibrosis Developmentmentioning
confidence: 98%
“…In addition, increased matrix protein synthesis and reduced matrix proteinase activity due to increased TGF-β activity can also contribute to the tumour ECM remodelling and result in desmoplasia, which is commonly found in many types of tumours, particularly pancreatic and renal cell carcinomas, as well as sarcomas [ 54 ]. In agreement, bone marrow-derived mesenchymal stem cells (BM-MSCs) have been shown to inhibit the TGF-β/SMAD pathway to repress hypoxia-inducible factor 1 subunit alpha (HIF-1α) and VEGF protein expression in the ECM to restrict liver fibrosis and early HCC tumourigenesis [ 55 ]. Similarly, pharmaceutical inhibition of the TGF-β signalling can promote the epithelial differentiation of human adipose-derived mesenchymal stem cells (ADSCs) during EMT through the downregulation of mesenchymal genes (e.g., Slug, zinc finger E-box binding homeobox 1 (ZEB1), integrin α5 (ITGA5), and vimentin (VIM)) and upregulation of epithelial genes (e.g., E-cadherin, epithelial cell adhesion molecule (EpCAM), zonula occludens-1 (ZO-1), occludin, deltaN p63 (δNp63), transcription factor 4 (TCF4), and Twist family bHLH transcription factor (TWIST)) to reverse EMT [ 56 ].…”
Section: Tgf-β In Cancer Initiation and Progressionmentioning
confidence: 99%